2010
DOI: 10.1099/mic.0.035063-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the Circulifer haematoceps cell line Ciha-1 by Spiroplasma citri: the non-insect-transmissible strain 44 is impaired in invasion

Abstract: Successful transmission of Spiroplasma citri by its leafhopper vector requires a specific interaction between the spiroplasma surface and the insect cells. With the aim of studying these interactions at the cellular and molecular levels, a cell line, named Ciha-1, was established using embryonic tissues from the eggs of the S. citri natural vector Circulifer haematoceps. This is the first report, to our knowledge, of a cell line for this leafhopper species and of its successful infection by the insect-transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The non-phagocytic cell line Ciha-1 established from C. haematoceps [12] was cultured at 32°C as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-phagocytic cell line Ciha-1 established from C. haematoceps [12] was cultured at 32°C as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
“…Successful transmission requires the spiroplasmas to pass through enterocytes of the mid-gut epithelium, multiply to high population in the hemocoel, and invade the salivary glands to be released in the saliva duct [7], [8]. Transmission electron microscopy (TEM) studies investigating invasion of insect cells in vivo and ex vivo both revealed invagination of the cell membrane in close contact with the spiroplasmas [9], [10], [11], [12], [13]. Together with the presence of spiroplasmas within membrane-bound cytoplasmic vesicles of insect cells [11], these observations strongly suggest an endocytosis mechanism mediated by receptor-ligand interactions [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation at 32°C for 1 week, the number of spiroplasma colonies on each plate was counted to estimate the number of Ciha-1 cells that had adherent spiroplasmas (4). In addition, treatment of spiroplasmas with trypsin alone in the absence of Ciha-1 cells had no effect on spiroplasma growth (18). The relative percentage of adhesion was calculated as follows: [(number of CFU for cells with protein treatment)/(number of CFU for untreated control cells)] ϫ 100%.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, protein overlay assays revealed that two membrane-associated proteins, a lipoprotein and the glycolytic enzyme phosphoglycerate kinase (PGK), interacted with actin in vitro. By use of the Ciha-1 leafhopper cell culture system (11), it was shown that PGK, by specifically binding to actin, was involved in internalization of spiroplasmas into insect cells (25). In contrast to these membraneassociated proteins, the pSci6_06 protein was predicted to be cytosolic, making a direct interaction with leafhopper cells unlikely.…”
Section: Discussionmentioning
confidence: 99%